Body weight changes, heamatological and serum biochemical properties of West African dwarf rams fed ginger fortified diets (2016)
The effect of feeding diets fortified with 0, 0.5, 1.0 and 1.5% ginger powder on body weight changes, haematological and serum biochemical properties and described as T1, T2, T3 and T4 respectively was determined using sixteen 12-18 months old WAD rams weighing 15.86 + 0.03kg. The animals were grouped into 4 treatments in a completely randomized design with 4 animals per treatment and fed the experimental diets for 28 days. Daily weight gain, feed intake and feed conversion ratio were monitored. Blood samples were collected and analyzed for haematological indices {Packed Cell Volume (PCV, %), Red Blood Cell (RBC, 10(6)/mm(3) and White Blood Cell (WBC, 10(3)/mm(3)} and biochemical parameters {Total protein (TP, g/dl), Blood urea nitrogen (BUN, mg/dl), Aspartate Transferase (AST, I.U. /I) and Alanine Transaminase (ALT, I.U. /1)}. PCV ranged from 33.75 (T4) to 39.00 (T2) and the values were within the recommended PCV value for WAD ram. Similarly, WBC values for rams on T4 (10.37) and T3 (8.80) were significantly higher than T2 (6.05) and Tl (4.87). Total protein and BUN increased linearly across the treatments. The values for AST and ALP ranged from 72.10 (T2) to 147.00 (T3) and 238.00 (T4) to 294.00 (T2) respectively. Consequently, it can be concluded that 1.5% fortification of ginger powder promoted body weight gain and had no deleterious effect on the haematological and serum biochemical profile of WAD rams.